2013
DOI: 10.1038/srep01469
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the layer thickness in plasmonic gold nanoparticles produced by thermal evaporation

Abstract: Metallic nanoparticles (NPs) have received recently considerable interest of photonic and photovoltaic communities. In this work, we report the optoelectronic properties of gold NPs (Au-NPs) obtained by depositing very thin gold layers on glass substrates through thermal evaporation electron-beam assisted process. The effect of mass thickness of the layer was evaluated. The polycrystalline Au-NPs, with grain sizes of 14 and 19 nm tend to be elongated in one direction as the mass thickness increase. A 2 nm laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
83
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 29 publications
13
83
0
Order By: Relevance
“…The broad decrease in transmission in the 550 nm−700 nm region is believed to be a result of a plasmon peak of the Au film. These results correspond well to the previously published data [37,38].…”
Section: Sputtering Deposition (supporting
confidence: 93%
See 1 more Smart Citation
“…The broad decrease in transmission in the 550 nm−700 nm region is believed to be a result of a plasmon peak of the Au film. These results correspond well to the previously published data [37,38].…”
Section: Sputtering Deposition (supporting
confidence: 93%
“…In the case of the sputtering, the highly uniform film can be obtained [37,38], while the attachment of the Au NPs to the SiO 2 mesoporous thin film results in the film structure that does not suppress the coupling of the higher order modes and thus retains the fringes in the transmission spectrum. The further work is required to understand this difference in more detail.…”
Section: Lbl Depositionmentioning
confidence: 99%
“…These observations correlate well with morphologies of thin metal fi lms obtained by sputtering [ 24 ] or thermal evaporation processes. [ 25 ] The effect of the distance between the two substrates on the transferred copper thickness is presented in Figure 3 . It was found that as the distance decreases, a thicker copper layer is transferred to the acceptor substrate, while the thickest layer was obtained without a gap.…”
Section: Doi: 101002/admi201400448mentioning
confidence: 99%
“…Therefore, efficient approaches of AuNP formation on substrates are necessary to achieve excellent NP distribution. For instance, self-assembled monolayers (SAMs), physical vapor deposition, and Langmuir-Blodgett method [6][7][8][9][10][11][12] have been developed to produce AuNPs on substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Physical vapor deposition can be used to produce AuNPs by depositing a layer of gold thin films followed by post-deposition annealing to acquire agglomerated AuNPs via the Ostwald ripening method [11]. However, diffusion of metals to form an interface layer and stacking of structures may degrade the memory properties of devices.…”
Section: Introductionmentioning
confidence: 99%